Systemic Immune-Inflammation Index (SII) and Neutrophil-to-Lymphocyte Ratio (NLR): A Strong Predictor of Disease Severity in Large-Artery Atherosclerosis (LAA) Stroke Patients - Liu K; Yang L; Liu Y; Zhang Y; Zhu J; Zhang H; He Z (Journal of Inflammation Research)
Keting Liu,1,2,* Li Yang,1,* Yang Liu,3 Yun Zhang,1 Juncheng Zhu,4 Haofeng Zhang,5 Zemin He6 1Department of Neurology, Chengdu Seventh People’s Hospital (Affiliated Cancer Hospital of Chengdu Medical College), Chengdu, Sichuan Province, 610213, People’s Republic of China; 2Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong Province, 510515, People’s Republic of China; 3Department of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, 610075, People’s Republic of China; 4Department of Radiology, Chengdu Seventh People’s Hospital (Affiliated Cancer Hospital of Chengdu Medical College), Chengdu, Sichuan Province, 610213, People’s Republic of China; 5Department of Information, Chengdu Seventh People’s Hospital (Affiliated Cancer Hospital of Chengdu Medical College), Chengdu, Sichuan Province, 610213, People’s Republic of China; 6Department of Thoracic Surgery, The First People’s Hospital of Shuangliu District (West China Airport Hospital of Sichuan University), Chendu, Sichuan Province, 610200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zemin He, Email 993092572@qq.comBackground: Systemic immune-inflammation index (SII) and neutrophil-to-lymphocyte ratio (NLR) are novel inflammatory markers based on neutrophil, platelet and lymphocyte counts. Atherosclerosis is a chronic inflammatory vascular disease. This study aimed to verify the predictive value of the clinical parameters such as systemic immune-inflammation index (SII) and neutrophil-to-lymphocyte ratio (NLR) for the severity in Large Artery Atherosclerosis (LAA) stroke patients.Methods: The SII is defined as platelet × (neutrophil count/lymphocyte count), the NLR is defined as neutrophil count/lymphocyte count. Univariate logistic regression was used to analyze the association between SII and NLR and NIHSS score in patients with LAA stroke. Multiple logistic regression was used to analyze the risk factors for the severity of LAA stroke. We plotted receiver operating characteristic curves to determine the diagnostic role of SII and NLR in differentiating stroke disease severity.Results: We included 283 LAA stroke patients, the SII and NLR in the moderate-to-severe stroke group were significantly higher than the mild stroke group. Multiple logistic regression analysis showed that SII (OR 1.051 95% CI (1.035– 1.066), P < 0.001), NLR (OR 1.077,95% CI (1.032– 1.123), P < 0.001) were significantly associated with stroke severity. The SII values under the receiver operating characteristic curve (0.701, 95% CI (0.649– 0.791, P < 0.001, cut-off value 912.97) and NLR values under the receiver operating characteristic curve (0.604,5% CI (0.519– 0.689), P < 0.01, cut-off value 1.461), and SII values had high discrimination ability. Both SII and NLR had high diagnostic and predictive value for stroke severity, and SII was better than NLR.Conclusion: The higher SII and NLR, the more severity in LAA stroke patients. SII and NLR are independent risk factors for LAA stroke, and they can also effectively predict stroke severity; moreover, SII has a higher diagnostic efficacy than NLR. However, multicenter studies with large sample size are still needed to confirm this conclusion.Keywords: large-artery atherosclerosis stroke, systemic immune-inflammation index, neutrophil-to-lymphocyte ratio, stroke severity, predictor